PENGEMBANGAN BAAMBOOZLE SEBAGAI MEDIA INTERAKSI MULTIDISPLIN SMP - Khusnah, Anggi Almirah; Alvia, Sarah; Lestari, Mawar; Sulistiawati , Ira; Ramadhani, Nia; Hamsiana, Hamsiana; Ningsih, Surya (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
This research is motivated by the low participation and interaction of students in the learning process due to the use of conventional methods that are not supported by interactive technology-based media. The focus of this research is the development of Baamboozle-based learning media as a means of multidisciplinary interaction to increase student activeness at SMPN 1 Wundulako. This research uses a participatory and collaborative approach involving 32 students, 3 teachers, and 6 female PLP students. The research procedure includes the stages of problem identification, planning, implementation, and evaluation. The instrument used is a student participation observation sheet with indicators of activeness in asking questions, answering questions, discussion involvement, and enthusiasm for learning. Data are analyzed descriptively quantitatively by comparing conditions before and after the use of the media. The results show that the use of Baamboozle can significantly increase student participation in all indicators, as well as creating a more interactive and enjoyable learning atmosphere. In addition, the multidisciplinary approach in this media also encourages increased critical thinking skills and contextual understanding of students. The conclusion of this research is that Baamboozle-based learning media is effective as a learning innovation to improve the quality of student interaction and participation, and has the potential to be developed and applied to various subjects and levels of education. ABSTRAK Penelitian ini dilatarbelakangi oleh rendahnya partisipasi dan interaksi siswa dalam proses pembelajaran akibat penggunaan metode konvensional yang belum didukung media berbasis teknologi interaktif. Fokus penelitian ini adalah pengembangan media pembelajaran berbasis Baamboozle sebagai sarana interaksi multidisiplin untuk meningkatkan keaktifan siswa di SMPN 1 Wundulako. Penelitian ini menggunakan pendekatan partisipatif dan kolaboratif dengan melibatkan 32 siswa, 3 guru, dan 6 mahasiswi PLP. Prosedur penelitian meliputi tahap identifikasi masalah, perencanaan, pelaksanaan, dan evaluasi. Instrumen yang digunakan berupa lembar observasi partisipasi siswa dengan indikator keaktifan bertanya, menjawab pertanyaan, keterlibatan diskusi, dan antusiasme belajar. Data dianalisis secara deskriptif kuantitatif dengan membandingkan kondisi sebelum dan sesudah penggunaan media. Hasil penelitian menunjukkan bahwa penggunaan Baamboozle mampu meningkatkan partisipasi siswa secara signifikan pada seluruh indikator, serta menciptakan suasana pembelajaran yang lebih interaktif dan menyenangkan. Selain itu, pendekatan multidisiplin dalam media ini juga mendorong peningkatan kemampuan berpikir kritis dan pemahaman kontekstual siswa. Simpulan penelitian ini adalah bahwa media pembelajaran berbasis Baamboozle efektif sebagai inovasi pembelajaran untuk meningkatkan kualitas interaksi dan partisipasi siswa, serta memiliki potensi untuk dikembangkan dan diterapkan pada berbagai mata pelajaran dan jenjang pendidikan.